PENGARUH METODE KATA LEMBAGA TERHADAP KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS II SEKOLAH DASAR - Ahmad, Arifin; Oktaviana, Fina; Meraldy; Adinda, Ramadhina; Nurulaini, Sekar (Cendikia: Jurnal Pendidikan dan Pengajaran, 2024)
This research was motivated by the low initial reading ability of students at SDN 239 Cigondewah. The aim of this research was to determine the effect of the institutional word method on the beginning reading ability of class II students at SDN 239 Cigondewah. The institutional word method is one way to overcome current problems. The subjects in this study consisted of two groups, namely the experimental class which was given treatment using the institutional word method and the control class which was the class without treatment. In both classes, assistance will be provided with the Indonesian language media kit available at the school. This research uses quantitative methods which are carried out by identifying problems, formulating problem statements, conveying the goals to be achieved, planning learning and then collecting data by carrying out learning activities in the class by providing evaluation questions at the end of the learning activities